HUBUNGAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 BANYUASIN III - Linda Sari; Abdurrahmansyah Abdurrahmansyah; Aida Imtihana (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
In the learning process that occurs in SMP Negeri 1 Banyuasin III, making students not accustomed to completing the tasks obtained by their own efforts because the occurrence of this process of learning independence is the lack of willingness in students to learn more actively and focus on the learning process. The purpose of this study was to determine the relationship between learning independence and learning outcomes of Grade VII students in Islamic Religion Education subjects at SMP Negeri 1 Banyuasin III. This type of research is quantitative research. The object of the informants in this study are the principal, Islamic Religious Education teachers and students of SMP Negeri 1 Banyuasin III. The type of data used is the type of quantitative data. There are two sources of data used, namely primary data obtained from principals, teachers and students, and secondary data derived from documents and literature that support this research. The data collection techniques in the form of observation, questionnaires and documentation. Then do the analysis using statistical analysis, namely the product moment correlation formula (Pearson) The results of this study with the known product moment correlation value is 0.552 and consulted with the